Music, movement and mood in Parkinson’s: A transdisciplinary study to develop a new protocol to measure functional mobility in people with Parkinson’s by integrating motion capture with a pressure sensitive gait mat - Köchli, Sabrina; Ungerer, Marietta; Rose, Dawn (Current Issues in Sport Science (CISS), 2023)
BackgroundParkinson’s disease (PD) is a neurodegenerative brain disorder associated with early-onset functional motor impairments (Rana et al., 2012). There are several assessment scales for the evaluation of PD, but many motor measurement protocols lack reference to the qualitative assessment of functional mobility in everyday life (Opara et al., 2017). Moreover, previous studies have shown that pharmaceutical treatments in combination with physical therapy play an important role in improving motor symptoms, but the benefits do not seem to extend to mental well-being (Fox et al., 2018). Growing evidence suggest that an interdisciplinary approach by integrating musical activity with exercises may have the potential to improve both functional mobility and psychological wellbeing (Barnish & Barran, 2020).MethodsThe first phase of this mixed methods study includes a Patient and Public Involvement (PPI) consultation process (workshops and interviews; Rose et al., 2022) to develop a context-appropriate new group-based intervention program for and with PwP and health professionals. The focus will lie on music activity and the use music imagery to develop individual jukeboxes of musical cues to combat motor symptoms such as rigidity and freeze of gait. To evaluate the efficacy and the generalisability of the program, a 12-week within-subject repeated measures controlled trial will be conducted in Switzerland and the UK. An accurate and reliable quantitative measurement protocol will be developed to enable assessment of disease progression, and evaluation of interventions alongside qualitative observations of mobility in PwP. Moreover, we aim to provide fine-grained assessment of clinical measures (such as the Timed Up and Go) using an integrated motion capture (MoCap) and gait mat analysis system.Expected Outcomes and PerspectivesThis project lays the foundation for the development of non-pharmaceutical and low-cost intervention programs. Our PPI approach will provide better individualised and targeted prevention strategies to counteract the increasing financial and personal burden of PD worldwide. A unique aspect of the study is to develop a new quantitative functional mobility measurement protocol to assess PwP over time. This research approach will contribute to our understanding of functional mobility symptoms and the use of music in PD to reduce symptom severity and improve quality of life.ReferencesBarnish, M. S., & Barran, S. M. (2020). A systematic review of active group-based dance, singing, music therapy and theatrical interventions for quality of life, functional communication, speech, motor function and cognitive status in people with Parkinson’s disease. BMC Neurology, 20(1), Article 371. https://doi.org/10.1186/s12883-020-01938-3Fox, S. H., Katzenschlager, R., Lim, S. Y., Barton, B., de Bie, R. M. A., Seppi, K., Coelho, M., & Sampaio, C. (2018). International Parkinson and movement disorder society evidence-based medicine review: Update on treatments for the motor symptoms of Parkinson’s disease. Movement Disorders, 33(8),1248-1266. https://doi.org/10.1002/mds.27372Opara, J., Małecki, A., Małecka, E., & Socha, T. (2017). Motor assessment in Parkinson’s disease. Annals of Agricultural and Environment Medicine, 24(3), 411-415. https://doi.org/10.5604/12321966.1232774Rana, A. Q., Siddiqui, I., & Yousuf, M. S. (2012). Challenges in diagnosis of young onset Parkinson’s disease. Journal of the Neurological Sciences, 323(1-2), 113-116. https://doi.org/10.1016/j.jns.2012.08.029Rose, D. C., Poliakoff, E., Hadley, R., Guérin, S. M. R., Phillips, M., & Young, W. R. (2022) Levelling the playing field: The role of workshops to explore how people with Parkinson’s use music for mood and movement management as part of a patient and public involvement strategy. Frontiers in Rehabilitation Sciences, 3, Article 873216. https://doi.org/10.3389/fresc.2022.873216